2011
DOI: 10.1007/s10802-011-9518-2
|View full text |Cite
|
Sign up to set email alerts
|

The Relation Between Maternal ADHD Symptoms & Improvement in Child Behavior Following Brief Behavioral Parent Training is Mediated by Change in Negative Parenting

Abstract: This study examined the extent to which maternal attention-deficit/hyperactivity disorder (ADHD) symptoms predict improvement in child behavior following brief behavioral parent training. Change in parenting was examined as a potential mediator of the negative relationship between maternal ADHD symptoms and improvement in child behavior. Seventy mothers of 6–10 year old children with ADHD underwent a comprehensive assessment of adult ADHD prior to participating in an abbreviated parent training program. Before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
99
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(117 citation statements)
references
References 47 publications
16
99
1
1
Order By: Relevance
“…First, results generally support previous intervention research with predominantly ADHD-C samples indicating that reductions in negative parenting following treatment mediate improvement of child impairment (e.g., Chronis et al, 2011; Hinshaw et al, 2000). Furthermore, given results suggesting that both inattention and positive/negative parenting related to impairment displayed by children with ADHD-I as observed by parents in the home setting, it appears that a multi-pronged treatment approach (e.g., targeting parenting skills and child symptoms) may be needed to produce meaningful outcomes in the various domains of functional impairment experienced by children with ADHD-I.…”
Section: Discussionsupporting
confidence: 81%
“…First, results generally support previous intervention research with predominantly ADHD-C samples indicating that reductions in negative parenting following treatment mediate improvement of child impairment (e.g., Chronis et al, 2011; Hinshaw et al, 2000). Furthermore, given results suggesting that both inattention and positive/negative parenting related to impairment displayed by children with ADHD-I as observed by parents in the home setting, it appears that a multi-pronged treatment approach (e.g., targeting parenting skills and child symptoms) may be needed to produce meaningful outcomes in the various domains of functional impairment experienced by children with ADHD-I.…”
Section: Discussionsupporting
confidence: 81%
“…behavioural and pharmacological) treatment. [29,44] Unfortunately, the presence of parental ADHD is associated with an attenuated response to behavioural treatments, [26,28,31] highlighting the need to screen (and, if necessary, treat) parents of youth with ADHD for adult ADHD. Thus, the presence of a child with ADHD should increase the clinician's suspicion of parental ADHD, which may be more subtle if not previously identified.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore no surprise that ADHD in parents is associated with an attenuated response to behavioural parent training programmes for children with ADHD. [26][27][28] In the National Institute of Mental Health (NIMH)-funded Multimodal Treatment Study of Children with ADHD (MTA), the combination of child stimulant treatment plus behaviour modification was associated with the most dramatic improvements in parenting and family interaction. [29] However, maternal psychopathology moderated response to both pharmacological and behavioural treatments, [30] and higher parental inattention predicted less child improvement at 3-year follow-up.…”
Section: Parental Adhd Negatively Impacts Evidence-based Treatments Fmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Chronis-Tuscano and colleagues (2011) found that 6–10 year old children of mothers who reported more ADHD symptoms displayed less improvement in their disruptive behavior symptoms immediately following BPT than did the children of parents reporting fewer ADHD symptoms. Like Sonuga-Barke and colleagues (2002), this study examined BPT only.…”
mentioning
confidence: 89%